Evaluasi Partisipatif untuk Penguatan Program Konservasi Karst Citatah dengan menggunakan The Most Significant Change (MSC) - Qodratulloh S, Waway; Putra, Tarekh Febriana; Nuzul, Dinda Amanda Ainun (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Forum Pemuda Peduli Karst Citatah (FP2KC) faces challenges in evaluating its environmental conservation programs in a structured and comprehensive manner. The evaluations of existing programs are still sporadic and insufficient to capture deeper social impacts because they rely heavily on quantitative data. To address this issue, a Community Service Program (PKM) was initiated with the aim of strengthening FP2KC’s evaluation capacity through the application of the Most Significant Change (MSC) method. This qualitative method was chosen for its ability to capture complex social changes through participants’ narratives. The approach enables a deeper and multidimensional understanding of program impacts, as demonstrated in various previous studies. The program’s implementation method includes four approaches: facilitation, FGDs and training, as well as mentoring and technical assistance. These approaches are intended to transfer knowledge and skills to FP2KC administrators, particularly in applying MSC. The outcomes of this program are innovations in program evaluation and enhanced partner skills. With a more effective evaluation system, FP2KC is expected to measure program progress more accountably and sustainably, while strategically contributing to the Sustainable Development Goals (SDGs) and the university’s Key Performance Indicators (KPIs).